The Influence of Online Learning during the Covid-19 Pandemic at SMA Muhammadiyah 3 Tulangan - Mufidah Nur Aliyyah; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
The purpose of this study is to find out how online learning is during the Covid-19 pandemic at SMA Muhammadiyah 3 Tulangan. This study uses descriptive qualitative research methods, namely by conducting direct observations and interviews about online learning with one of the teachers at the school. The results of the study concluded that learning during the pandemic at the school affected the continuity of the teaching and learning process, however, online learning at the school went well and was conducive despite the many difficulties experienced by some teachers